KEANEKARAGAMAN SUKU PANDANACEAE DI PEGUNUNGAN SEKITAR DESA SEDOA, KAWASAN TAMAN NASIONAL LORE LINDU KABUPATEN POSO-PROPINSI SULAWESI TENGAH - Ary Prihardhyanto Keim; Himmah Rustiami (BERITA BIOLOGI, 2007)
The diversity of the pandan flora from the Lore Lindu National Park has never been reported. Recent floristic study recognised 6 species belonging to Pandanaceae occur in the area. Freycinetia minahassae, F.celebica and Pandanus sarasinorum are the common species found in Sulawesi. Freycinetia oblanceolata and F. polystachya are new records.Freycinetia celebica is rediscovered. The endemic states of F.minahassae and P.sarasinorum are toppled. The extended distribution area of P. gladiator is recorded.